Interaction between α-Melanocyte-Stimulating Hormone and Corticotropin-Releasing Hormone in the Regulation of Feeding and Hypothalamo-Pituitary-Adrenal Responses - Lu, Xin-Yun (J Neurosci, 2003)
Both central α-melanocyte-stimulating hormone and corticotropin-releasing hormone (CRH) have been implicated in feeding and neuroendocrine mechanisms. The anatomical overlap and functional similarities between these two neurotransmitter systems led to the hypothesis that CRH might act as one of the mediators of the central actions of the melanocortin system. By double-labeling in situ hybridization, a subpopulation of CRH neurons in the paraventricular nucleus of the hypothalamus (PVN) were shown to contain the melanocortin-4 receptor (MC4R), concentrated in the ventromedial part of the parvicellular PVN (up to 33%). Intracerebroventricular injection of melanocortin agonist MTII to conscious and freely moving rats induced a rapid induction of CRH gene transcription in the PVN. This effect was accompanied by a rise in plasma corticosterone levels in a dose- and time-dependent manner, with the maximum response observed 30 min after MTII injection. MTII (0.5 nmol)-induced increase in plasma corticosterone was attenuated by the selective MC4R antagonist HS014 (0.25-1.0 nmol) and nonselective CRH receptor antagonist α-helical-CRH(9-41) (0.125-0.5 nmol) in a dose-dependent manner. Moreover, the anorectic effect of MTII was evaluated at 1, 2, and 24 hr after intracerebroventricular injection. Approximately half of the inhibitory effect of MTII (0.5 nmol) on food intake was reversed by pretreatment withα-helical-CRH(9-41) at 0.25 and 0.5 nmol doses. Collectively, these results provide evidence that CRH acts as a downstream mediator of melanocortin signaling and contributes to the mechanisms by which the central melanocortin system controls feeding and neuroendocrine responses.